2019
DOI: 10.1007/s10162-019-00722-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Medial Olivocochlear Efferents on the Detection of Amplitude Modulation for Tones Presented in Noise

Abstract: The medial olivocochlear reflex has been hypothesized to improve the detection and discrimination of dynamic signals in noisy backgrounds. This hypothesis was tested here by comparing behavioral outcomes with otoacoustic emissions. The effects of a precursor on amplitude-modulation (AM) detection were measured for a 1-and 6-kHz carrier at levels of 40, 60, and 80 dB SPL in a two-octave-wide noise masker with a level designed to produce poor, but above-chance, performance. Three types of precursor were used: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Finally, our model does not include neural adaptation to stimulus statistics as a potential contributing factor to speech-in-noise discrimination [ 86 , 87 ]. We therefore cannot discount its involvement in the lexical decision task nor show that it is sufficient for robust recognition of degraded speech without the MOC reflex as has been previously suggested [ 86 , 87 , 148 ].…”
Section: Discussionmentioning
confidence: 77%
“…Finally, our model does not include neural adaptation to stimulus statistics as a potential contributing factor to speech-in-noise discrimination [ 86 , 87 ]. We therefore cannot discount its involvement in the lexical decision task nor show that it is sufficient for robust recognition of degraded speech without the MOC reflex as has been previously suggested [ 86 , 87 , 148 ].…”
Section: Discussionmentioning
confidence: 77%
“…This conclusion is supported by two other studies. Wojtczak et al (2019) showed that AM sensitivity in noise can improve with a precursor even when the precursor does not change basilar membrane responses (i.e., when it does not activate the MOCR). Second, cochlear-implant users show adaptation to noise in word recognition despite lacking MOCR effects (Marrufo-Pérez et al, 2018), which suggests that mechanisms different from the MOCR can facilitate speech-innoise recognition, at least when the MOCR is absent.…”
Section: Discussionmentioning
confidence: 99%
“…This variability has generally been attributed to methodological differences in OAE measurement (see [78] for review). Still, more recent studies have questioned whether suppression of cochlear gain by the MOC reflex actually benefits hearing in noise: proposing either a contribution of the reflex to perception only at specific SNRs [24, 78] or, in extremis , that the MOC reflex plays no role, and that neural adaptation to noise statistics may instead underlay robust recognition of degraded speech [73,79,80].…”
Section: Discussionmentioning
confidence: 99%